Inquiry-Based Learning Videos as Effective Media for Grade IV Elementary School Science Learning - Cok Gede Agung Ratmaja Dharma Putra; A.A Gede Agung; Ida Bagus Gede Surya Abadi (Jurnal Pendidikan Multikultural Indonesia, 2025)
The limited use of innovative learning media in science and social studies (IPAS) instruction often causes students to experience boredom and reduced engagement during the learning process. This condition negatively affects students’ conceptual understanding, particularly in learning topics related to diversity and cultural preservation that require contextual and meaningful learning approaches. This study aims to analyze the design, evaluate the quality, and examine the effectiveness of an Inquiry Learning based instructional video as a learning medium for fourth-grade IPAS learning. This research employed a development research design using the ADDIE model. The study involved 37 fourth-grade students as research subjects. Data were collected through questionnaires and achievement tests using expert validation sheets and learning outcome assessment instruments. The data were analyzed using descriptive quantitative techniques and correlated t-test analysis. The findings indicate that the developed instructional video demonstrates very high quality based on expert validation and user trials, and conceptually proves effective in improving students’ conceptual understanding, learning engagement, and their ability to connect learning materials with real-life contexts. These results imply that Inquiry Learning based instructional videos function as innovative learning media that support interactive, contextual, and student-centered IPAS instruction, thereby contributing to the sustainable improvement of learning processes and outcomes in elementary education.